Ilian, I. y Šabec, M. (2024). "Pablo Neruda en el espejo del socialismo". Bruselas: Peter Lang Verlag. - Pablo Sánchez (América sin Nombre)
Reseña del libro Ilian, I. y Šabec, M. (2024). Pablo Neruda en el espejo del socialismo. Bruselas: Peter Lang Verlag, 432 pp, ISBN: 9783034349055